6-latki ze specjalnymi potrzebami edukacyjnymi na starcie szkolnym. Studium różnicy płci w kontekście reformy oświaty - Buchnat, Marzena; Chmura-Rutkowska, Iwona (Wydawnictwo Naukowe UAM, 2013)
Initiators of the most socially negotiated changes under the current reform of the education system, including the lowering of school age to 6, indicate “bridging the education gap” as one of the advantages of an earlier education. In fact, there is no critical refl ection and discussion on how the education system responds to the diversity of children’s needs and identifi ed areas and risk factors of educational failures on the threshold of school. In the text we pay special attention to two important issues overlooked in the ministerial discourse: a risk factor for school failure defi ned as special educational needs (SEN) and the problem of differentiation of the level of preparedness, experience and school achievements of children based on gender, with particular regard to socioemotional development.
6-year old children with special educational needs at the beginning of school. A study of gender in the context of education reform
Keywords: special educational needs; school adaptation; school readiness; gender and education; gender stereotypes